ANALISIS MANAJEMEN RUMAH POTONG HEWAN KECAMATAN TAMPAN KOTA PEKANBARU DAN DAMPAKNYA TERHADAP LINGKUNGAN - Clara Shinta; Bintal Amin; Mubarak Mubarak (Jurnal Ilmu Lingkungan, 2021)
Slaughterhouse is a service unit for the provision  of safe, healthy, whole and halal meat that is ready to be marketed to the public. To produce safe, healthy, whole and halal meat , the slaughterhouse must fulfill several aspects, namely technical aspects, technological aspects and environmental aspects.   The research aims to observe the management of the RPH Tampan District, Pekanbaru City from the technical, technological and environmental aspects . The research method used is the survey method to find out that the slaughterhouse has the standards met  according to the Decision of the Minister of Agriculture No. 13 / Permentan / OT.140 / 1/2010 concerning the requirements for Slaughterhouses and the impact on the surrounding community as well as the T test method on analyzing the quality of wastewater. The result of this research is RPH (1) RPH does not fulfill the Decision of the Minister of Agriculture No. 13 / Permentan / OT.140 / 1/2010 concerning the requirements of slaughterhouses (2) the quality of liquid waste does not meet quality standards (3) the slaughterhouse has a negative impact on the surrounding environment. The conclusion of this study that slaughterhouse the does not meet the standards for operation because it is close to residential areas, does not have NKV ( Veterinary Control Number ) and the quality of liquid waste that disturbs the surrounding environment.